2016
DOI: 10.1016/j.rppede.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of community-acquired infections of lower airways among infants

Abstract: Objective:To estimate the incidence of community-acquired infections of the lower respiratory tract and the risk factors associated with its occurrence in infants, in their first year of life.Methods:A prospective cohort study of infants who were followed up during the first 12 months of life. Interviews were conducted with their mothers, and children were clinically monitored bimonthly to investigate the occurrence of the incidence density of community-acquired infections of the lower respiratory tract. Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
1
8
0
5
Order By: Relevance
“…A study conducted in Jataí, GO, found that the prevalence of antibiotic use in the last month in children aged 0-4 years was 11%, reaching 59% and for those in the income range of 1-3 minimum wages 25 . In the present study, using educational level as socioeconomic indicator, it was found that children whose mothers had higher educational level had lower prevalence of antibiotic prescription.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Jataí, GO, found that the prevalence of antibiotic use in the last month in children aged 0-4 years was 11%, reaching 59% and for those in the income range of 1-3 minimum wages 25 . In the present study, using educational level as socioeconomic indicator, it was found that children whose mothers had higher educational level had lower prevalence of antibiotic prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Estas são caracterizadas por rinofaringites virais, faringoamigdalites virais e bacterianas, hipertrofia de amígdalas e adenóides, otite média aguda, sinusite, obstrução inflamatória aguda das VA, enquanto aquelas incluem principalmente bronquite, bronquiolite e pneumonias. Outro distúrbio infeccioso é a coqueluche (MAIA et al, 2014). Os distúrbios respiratórios, a partir do século XX, caracterizaram-se como a maior causa de mortalidade na infância, principalmente em menores de cinco anos (PRATO et al, 2014).…”
Section: Introductionunclassified
“…Os distúrbios respiratórios, a partir do século XX, caracterizaram-se como a maior causa de mortalidade na infância, principalmente em menores de cinco anos (PRATO et al, 2014). Na América Latina, as infecções respiratórias foram responsáveis por mais de 80.000 mortes de crianças por ano, 40% ocorreram no Brasil (MARTINS et al, 2016). As Infecções de Vias Aéreas superiores (IVAS) representam um importante fator preditor de saúde pública devido serem as principais causas de consulta médica no ambiente hospitalar e unidades básicas de saúde no primeiro ano de vida, além do alto absenteísmo escolar (CARVALHO;PEREIRA, 2002).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Pneumonia poses a significant threat to the lives of children below five years worldwide, contributing to a high number of hospitalizations and death [1][2][3] . Morbidity and morbidity is especially common in children under five and the elderly, although any age group can be affected 4,5 .…”
Section: Introductionmentioning
confidence: 99%